A Randomized Phase II Study of Sequential Eribulin Versus Paclitaxel Followed by FAC/FEC as Neoadjuvant Therapy in Patients with Operable HER2‐Negative Breast Cancer. (16th December 2020) - Lim, Bora; Song, Juhee; Ibrahim, Nuhad K.; Koenig, Kimberly B.; Chavez‐MacGregor, Mariana; Ensor, Joe E.; Gomez, Jill Schwartz; Krishnamurthy, Savitri; Caudle, Abigail S.; Shaitelman, Simona F.; Whitman, Gary J.; Valero, Vicente
Abstract: Lessons Learned: The combination of eribulin with 5‐fluorouracil, either doxorubicin or epirubicin, and cyclophosphamide (FAC/FEC) was not superior to the combination of paclitaxel with FAC/FEC and was associated with greater hematologic toxicity. Eribulin followed by an anthracycline‐based regimen is not recommended as a standard neoadjuvant therapy in nonmetastatic operable breast cancer. Background: Neoadjuvant systemic therapy is the standard of care for locally advanced operable breast cancer. We hypothesized eribulin may improve the pathological complete response (pCR) rate compared with paclitaxel. Methods: We conducted a 1:1 randomized open‐label phase II study comparing eribulin versus paclitaxel followed by 5‐fluorouracil, either doxorubicin or epirubicin, and cyclophosphamide (FAC/FEC) in patients with operable HER2‐negative breast cancer. pCR and toxicity of paclitaxel 80 mg/m 2 weekly for 12 doses or eribulin 1.4 mg/m 2 on days 1 and 8 of a 21‐day cycle for 4 cycles followed by FAC/FEC were compared. Results: At the interim futility analysis, in March 2015, 51 patients (28 paclitaxel, 23 eribulin) had received at least one dose of the study drug and were thus evaluable for toxicity; of these, 47 (26 paclitaxel, 21 eribulin) had undergone surgery and were thus evaluable for efficacy. Seven of 26 (27%) in the paclitaxel group and 1 of 21 (5%) in the eribulin group achieved a pCR, and this result crossed a futility stopping boundary. In the paclitaxel group, the most common serious adverse events (SAEs) were neutropenic fever (grade 3, 3 patients, 11%). In the eribulin group, nine patients (39%) had neutropenia‐related SAEs, and one died of neutropenic sepsis. The study was thus discontinued. For the paclitaxel and eribulin groups, the 5‐year event‐free survival (EFS) rates were 81.8% and 74.0% (hazard ratio [HR], 1.549; 95% confidence interval [CI], 0.817–2.938; p = .3767), and the 5‐year overall survival (OS) rates were 100% and 84.4% (HR, 5.813; 95% CI, 0.647–52.208; p = .0752), respectively. Conclusion: We did not observe a higher proportion of patients undergoing breast conservation surgery in the eribulin group than in the paclitaxel group. The patients treated with eribulin were more likely to undergo mastectomy and less likely to undergo breast conservation surgery, but the difference was not statistically significant. As neoadjuvant therapy for operable HER2‐negative breast cancer, eribulin followed by FAC/FEC is not superior to paclitaxel followed by FAC/FEC and is associated with a higher incidence of neutropenia‐related serious adverse events.